Novel Synthesis of Titanium Oxide Nanoparticles: Biological Activity and Acute Toxicity Study - Moaaz T. Hamed; Basant A. Bakr; Yahya H. Shahin; Bassma H. Elwakil; Marwa M. Abu-Serie; Faizah S. Aljohani; Adnan A. Bekhit (Bioinorganic Chemistry and Applications)
Titanium oxide nanoparticles (TiO2 NPs) have been attracting numerous research studies due to their activity; however, there is a growing concern about the corresponding toxicity. Here in the present study, titanium oxide nanoparticles were newly synthesized using propolis extract followed by antimicrobial activity, cytotoxicity assay using human cancer cell lines, and acute toxicity study. The physicochemical characterization of the newly synthesized TiO2 NPs had average size = 57.5 nm, PdI = 0.308, and zeta potential = −32.4 mV. Antimicrobial activity assessment proved the superior activity against Gram-positive compared to Gram-negative bacteria and yeast (lowest MIC values 8, 32, and 32, respectively). The newly synthesized TiO2 NPs showed a potent activity against the following human cancer cell lines: liver (HepG-2) (IC50 8.5 µg/mL), colon (Caco-2), and breast (MDA-MB 231) (IC50 11.0 and 18.7 µg/mL). In vivo acute toxicity study was conducted using low (10 mg/kg) and high (1000 mg/kg) doses of the synthesized TiO2 NPs in albino male rats. Biochemistry and histopathology of the liver, kidney, and brain proved the safety of the synthesized TiO2 NPs at low dose while at high dose, there was TiO2 NPs deposit in different vital organs except the cerebral tissue.